Domain Storytelling : a Collaborative, Visual, and Agile Way to Build Domain-Driven Software - Hofer, Stefan; Schwentner, Henning (Addison-Wesley Professional, 2021)
Rapidly Understand New Domains, So You Can Build Great Software for Them Using Domain Storytelling, you can quickly gain clarity about a new domain's people, tasks, tools, work items, and events, avoiding costly misunderstandings and building better software. In Domain Storytelling, the method's inventors show how domain experts can clearly tell their stories, capture their insights with simple pictographs, show their work, get feedback, and get everyone on the same page. Stefan Hofer and Henning Schwentner explain how and why Domain Storytelling works. They introduce the method's easy pictographic language, scenario-based modeling techniques, workshop format, and relationship to other modeling methods. And using step-by-step case studies, they guide you through solving many common problems, from creating new domain languages to deriving requirements, optimizing workflows to uncovering "shadow IT." Fully align all project participants and stakeholders, both technical and business-focused Master a simple set of symbols and rules for modeling any process or workflow Use workshop-based collaborative modeling to find better solutions faster Organize domains for manageability, and transform domain knowledge into requirements Move your models from diagrams and sticky notes to code Make better decisions about whether to build or buy software Gain better visibility into your IT landscape so you can consolidate or optimize it This guide is for everyone who wants more effective software -- from developers, architects, and team leads to the domain experts and executives who rely on it every day